Sensitivity analysis and integrated optimization of placement and parameters of rotational friction dampers based on seismic energy approach considering soil-structure interaction - Hossein Jarrahi; S. Javad Vaziri; Mohsen Khatibinia (PLoS ONE, 2025)
The optimization of seismic resilience in steel moment-resisting frames (SMRFs) has driven extensive research into passive energy dissipation systems, particularly rotational friction dampers (RFDs). This study introduces a novel hybrid optimization framework that simultaneously determines the optimal placement and design parameters of RFDs in SMRFs. A sensitivity analysis of key RFD parameters, including frictional moment and rigid beam length, highlights their influence on seismic performance. The optimization problem is formulated based on the seismic energy dissipation concept, employing a modified binary and real-coded particle swarm optimization (BRPSO) algorithm. The study examines both 6- and 10-story SMRFs under artificial earthquake records, incorporating soil-structure interaction (SSI) effects to enhance accuracy. The results reveal that the optimal distribution of RFDs significantly reduces structural hysteretic energy and inter-story drift while improving energy dissipation efficiency. A comparative analysis shows that, for both SMRF configurations, an increase in the number of RFDs beyond the optimal threshold yields diminishing benefits in seismic mitigation. The proposed framework not only enhances structural resilience but also minimizes construction costs by ensuring an efficient damper layout. These findings provide valuable insights for designing cost-effective and high-performance seismic protection strategies for mid- to high-rise structures.